Time interval between hCG administration and oocyte retrieval and ART outcomes: an updated systematic review and meta-analysis - Runxin Gan; Xi Huang; Jing Zhao; Qiong Zhang; Chuan Huang; Yanping Li (BMC, 2023)
Abstract Research question To explore whether prolonged hCG-ovum pickup interval improves assisted reproductive technology outcomes. Design CENTRAL, CNKI, Cochrane Systematic Reviews, EMBASE, MEDLINE, PUBMED, and Web of Science up to May 13 2023 were searched for studies reporting associations between hCG-ovum pickup intervals and assisted reproductive technology outcomes. Intervention types included short (≤ 36 h) and long (> 36 h) hCG-ovum pickup intervals in assisted reproductive technology cycles. All outcomes were based upon only fresh embryo transfers. Primary outcome is defined as the clinical pregnancy rate. Data were pooled using random-effects models. Heterogeneity was assessed using the I 2 statistics. Results Twelve studies were included in the meta-analysis, including five retrospective cohort studies, one prospective cohort study, and six randomized or quasi-randomized controlled trials. The short and long interval groups had similar oocyte maturation rates, fertilization rate and high-quality embryo rate (OR, 0.69; 95% CI, 0.45-1.06; I 2 = 91.1%, OR, 0.88; 95% CI, 0.77-1.0; I 2 = 44.4% and OR, 1.05; 95% CI, 0.95-1.17; I 2 = 8.6%, respectively). The clinical pregnancy rates in the long retrieval group were significantly higher than in the short retrieval group (OR, 0.66; 95% CI, 0.45-0.95; I 2 = 35.4%). The groups had similar miscarriage and live birth rates (OR, 1.92; 95% CI, 0.66-5.60; I 2 = 0.0% and OR, 0.50; 95% CI, 0.24-1.04; I 2 = 0.0%, respectively). Conclusions The clinical pregnancy rates can be increased by prolonging the hCG-ovum pickup interval, which would help us develop more reasonable time schedules for fertility centers and patients. Meta-analysis registration PROSPERO CRD42022310006 (28 Apr 2022).